2017
DOI: 10.1155/2017/9385716
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Potato Consumption in Slovak Region Contaminated by Heavy Metals due to Previous Mining Activity

Abstract: Heavy metals are among the most serious environmental contaminants in mining districts. Soil, as one of the main components of the environment, is the place of heavy metal entry into plants and consequently into the food chain, too. Potatoes grown in the region of Middle Spis (Slovakia) may be a source of increased content of heavy metals and pose a health risk to the consumer. The contents of heavy metals (Cd, Pb, and Ni) in potato and soil samples were determined using the AAS method and compared with limit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
1
6
1
Order By: Relevance
“…shows the results of the heavy metals content in tubers of both native potato varieties collected in the four districts and obtained from the same soil sampling sites. Values obtained were compared to the maximum levels recom-Heavy metals concentrations in tubers of two native potato varieties (mg/kg) in four highland Andean locations in Junín, Peru.Slovakia and Jamaica report indicate lower values[2] [50] coincident with what was found in this study. In Punjab, Pakistan[22] reports indicate high Pb contents in potato that exceed 40 times the allowed limit, while our study determined that Pb exceeds four times what is recommended.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…shows the results of the heavy metals content in tubers of both native potato varieties collected in the four districts and obtained from the same soil sampling sites. Values obtained were compared to the maximum levels recom-Heavy metals concentrations in tubers of two native potato varieties (mg/kg) in four highland Andean locations in Junín, Peru.Slovakia and Jamaica report indicate lower values[2] [50] coincident with what was found in this study. In Punjab, Pakistan[22] reports indicate high Pb contents in potato that exceed 40 times the allowed limit, while our study determined that Pb exceeds four times what is recommended.…”
supporting
confidence: 92%
“…Heavy metals represent a source of contamination and an environmental and human health problem [1]. The soil is the entry point for heavy metals in plants and, consequently, also in the food chain [2]. There are different sources of heavy metals in the soil such as natural sources and anthropogenic sources (mining and industrial activities, irrigation with sewage and the excessive use of pesticides and fertilizers) [3] [4] [5].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the contents of Cd and Pb in a mining area of Shanxi in China and in Slovakia were higher in the surface soil (Li et al 2015b;Musilova et al 2017). This occurred because mining areas contain a great deal of heavy metal-polluted dust, which will float down to the surrounding environment (Galiulin et al 2002) and cause heavy metal pollution in the surface soil though wind and transport.…”
Section: Characteristics Of Heavy Metal and Environmental Effect In Tmentioning
confidence: 98%
“…Another study found potatoes in Junin showed levels of Pb at 0.41 mg/kg (MCL at 0.1 mg/kg) [ 68 ] The authors explained that mining was a likely source of this contamination. Similarly, other studies in Chile, China, and Slovakia reported that produce grown near a mining operation had noncompliant concentrations of As, Pb, and Cd [ 70 , 71 , 72 ]. These findings supported the importance of understanding the risk of contamination of produce grown close to mining activities.…”
Section: Chemical Contaminantsmentioning
confidence: 74%